Levels of multiple proteins in gingival crevicular fluid and intra-amniotic complications in women with preterm prelabor rupture of membranes. (2nd October 2018) - Kacerovsky, Marian; Radochova, Vladimira; Musilova, Ivana; Stepan, Martin; Slezak, Radovan; Andrys, Ctirad; Skogstrand, Kristin; Hougaard, David; Jacobsson, Bo
Abstract: Objective: The primary aim of this study was to identify the association between the local inflammatory response in gingival crevicular fluid measured by the levels of multiple proteins and maternal and intra-amniotic inflammatory responses measured by maternal serum C-reactive protein (CRP) and amniotic fluid interleukin (IL)-6 concentrations, respectively, in women with preterm prelabor rupture of membranes (PPROM). Methods: A prospective study was performed in which 78 women with singleton pregnancies complicated by PPROM between 24 + 0 and 36 + 6 weeks of gestation were included. Transabdominal amniocenteses were performed at the time of admission. A bedside assessment of amniotic fluid IL-6 was performed. Maternal serum CRP concentration was also measured at the time of admission. Gingival crevicular fluid was collected from the pocket of the selected tooth (the tooth with the deepest pocket) using standard sterile paper strips within 72 h after admission. Twenty-six proteins in the gingival crevicular fluid were assessed by multiplex the Meso-Scale technology. Results: No correlations between the levels of proteins in the gingival crevicular fluid and maternal serum CRP and amniotic fluid IL-6 concentrations were found, except for a weak positive correlation between granulocyte macrophage colony-stimulating factor and CRP. Conclusions: The local inflammatory response in the gingival crevicular fluid is not related to the maternal and intra-amniotic inflammatory responses in women with PPROM.